Hungarian Monitoring, 16 February 1988 . [Magyar rádiófigyelő], 1988. február 16 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Howe in Moscow - After the Common Market summit in Brussels - Press conference of Polish government spokesman - Waldheim's television speech Domestic Affairs: - Gromyko visits Hungary - Hungarian church delegation in Moscow - Pollution in Monor - Hospitals now already accepting paying patients Economy: - International global economic conference has begun in Budapest - The most viable farming unit: the small cooperative - Salgótarján Glass Factory ships glasses to McDonnell-Douglas in exchange for agricultural helicopters Külpolitika: - Howe Moszkvában - A Közös Piac brüsszeli csúcsértekezlete után - Lengyel kormányszóvivő sajtóértekezlete - Waldheim TV beszéde Belpolitika: - Gromiko Magyarországra látogat - Magyar egyházi küldöttség Moszkvában - Monori környezetszennyezés - A kórházak már fogadják a fizetős pacienseket is Gazdaság: - Nemzetközi világgazdasági konferencia kezdődött Budapesten - A legéletképesebb gazdálkodási forma: a kisszövetkezet - A Salgótarjáni Öblösüveggyár poharat szállít a McDonnell Douglas cégnek mezőgazdasági helikopterek fejében